2019
DOI: 10.13189/ujer.2019.070810
|View full text |Cite
|
Sign up to set email alerts
|

"Tundang" Folk Songs of West Kalimantan Indonesia as Material of Local Wisdom Based Education

Abstract: This article describes the use, function and development of the folk songs of West Kalimantan, Tundang the supporting community by relating them to the cultural elements. Tundang, as one of the oral folklore in folk songs, can be used for learning in schools with cooperation between the teachers and the students. The preservation of the songs of the people of West Kalimantan can make changes to the preservation of other cultures by elevating them to a performance art that can be developed, namely increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The findings of this research are consistent with previous studies that have shown that the use of local cultural contexts in education can enhance students' learning interest and outcomes (Ayurachmawati et al, 2022;Hanafie Das et al, 2022;Pane et al, 2022). Previous research has found that a local wisdombased learning approach helps students engage in a more effective learning process (Hasna N, 2023;Wulan et al, 2019). Other studies have also proven that developing instructional materials based on local wisdom is effective in enhancing students' learning outcomes (Azizah & Alnashr, 2022;Rahayu et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this research are consistent with previous studies that have shown that the use of local cultural contexts in education can enhance students' learning interest and outcomes (Ayurachmawati et al, 2022;Hanafie Das et al, 2022;Pane et al, 2022). Previous research has found that a local wisdombased learning approach helps students engage in a more effective learning process (Hasna N, 2023;Wulan et al, 2019). Other studies have also proven that developing instructional materials based on local wisdom is effective in enhancing students' learning outcomes (Azizah & Alnashr, 2022;Rahayu et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al (2022) discussed the inheritance and development of folk song culture in the process of modernization. Wulan et al (2019) pointed out that globalization and modernization provide opportunities for the spread and development of local folk songs. Secondly, some literature focuses on the adaptation and innovation of folk songs in social changes.…”
Section: Subjects Categories and Locationsmentioning
confidence: 99%
“…There are also some studies that have achieved effective organization and dissemination of folk song materials by creating databases and using technologies such as machine learning (Huang & Song, 2022;Sabirova, 2020). Wulan et al (2019) discussed the opportunities provided by globalization and modernization for the dissemination and development of local folk songs. Through international cultural exchange projects, folk songs from different countries and regions can be known and appreciated on a wider scale, thereby increasing the possibility of the spread and protection of folk songs (Wulan et al, 2019;Zuo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of human creativity, tundang reflects the values, ideas, dreams, philosophy, and collective consciousness of those who create it, literally and allegorically. It also expresses, intentionally or unintentionally, how a collaborative community thinks, acts, and behaves, manifesting various mental attitudes, mindsets, and values and immortalizing things developed in the form of a questionable rhyme (Wulan et al, 2019). Nugroho (2021) investigated Sumba folk songs.…”
Section: Introductionmentioning
confidence: 99%